Apostasy and religious freedom: a response to Thio Li-ann - Ab Aziz, Shamrahayu (LexisNexis, 2007)
Article 'Apostasy and Religious Freedom: Constitutional Issues Arising from the Lina Joy Litigation' by Thio Li-ann has given rise to several points of interest. While the essay was a commentary on the constitutional issues arising from the Lina Joy decisions, some issues need to be discussed further: primarily on the scope of religious freedom under the Federal Constitution, the relationship between religious freedom and the position of Islam, the position of Islamic criminal law under the Federal Constitution, religious freedom in multi-religious Malaysia, the religious or secular character of the country and the application of international principles in interpreting the right to religious freedom in Malaysia.